A two-day professional development workshop on advanced nutrition support increased Ghanaian nutrition and dietetic professionals' self-efficacy and practical knowledge of enteral and parenteral nutrition support. - Ayande, Ruthfirst EA; Agordoh, Percival D; Salino, Vanessa J; Webster-Ariyan, Clarisa; Collier, Lindsay; Asante, Matilda; Carbone, Elena T (South African Journal of Clinical Nutrition, 2025)
Aims: Enteral and parenteral nutrition support (NS) improves clinical outcomes in critically ill patients, yet evidence from a needs assessment indicates that Ghanaian clinical nutrition practitioners (CNPs) have low self-efficacy in administering NS, especially parenteral nutrition. This study aimed to assess changes in knowledge and self-efficacy of Ghanaian CNPs on enteral and parenteral NS following a continuous professional development (CPD) workshop. Methods: A one-group pre-test/post-test study was used. Remote workshops curated in July 2022 and designed to meet predetermined needs were delivered over two days by registered dietitians and certified nutrition support clinicians. CNPs' self-efficacy was assessed using a 5-point Likert scale. Practical knowledge was assessed using 7 short case scenarios for indications of enteral and parenteral NS, and open-ended questions were used to request additional qualitative information concerning self-efficacy scores. Paired-sample t-tests were used to compare pre- and post-survey scores, and qualitative data were thematized. Results: Fifty-two participants completed both surveys. There were statistically significant increases in self-efficacy for enteral and parenteral NS delivery, including: assessing indications for enteral nutrition (EN) (d = 0.62 CI 0.30, 0.94); writing EN prescriptions (d = 0.71 CI 0.38, 1.04) and determining micronutrient additives for parenteral nutrition (PN) (d = 1.07 CI 0.70, 1.44) as well as increases in knowledge based on the practical case studies (d = 0.29 CI 0.01, 0.57). In-depth understanding of EN and PN guidelines and feelings of empowerment were identified as reasons for increased self-efficacy and practical knowledge. Conclusion: CPD workshops are a good first step to bridge gaps in the delivery of NS by Ghanaian CNPs; however, additional practical training modules are needed to improve practitioners' competencies in the delivery of NS.